Development of a Trait and Factor Counseling Guide to Improve Junior High School Students' Career Decision-Making Skills - Simon Wudy; I Ketut Gading; Putu Ari Dharmayanti; Nyoman Dantes; I Ketut Dharsana; Ni Ketut Suarni (Bisma The Journal of Counseling, 2025)
The low level of career decision-making ability among lower secondary students remains a critical issue, as it can hinder the formation of career pathways aligned with their interests and potential. Limited knowledge, insufficient information, and unclear career insights often lead to anxiety and uncertainty when students are required to make career-related choices, indicating the need for a structured and theory-based counselling intervention. This study aims to analyze the implementation procedures of Trait and Factor counselling services and to evaluate the content validity of the developed counselling guidebook. The research employed a development design using the 4D model. Participants included counselling experts, guidance and counselling teachers, and students involved in the limited trial phase. Data were collected through questionnaires using a content validity assessment instrument. The data were analyzed using content validity techniques and effectiveness testing through pre- and post-intervention assessments. The findings indicate that the Trait and Factor counselling guidebook possesses strong relevance and high content validity based on expert judgments, making it feasible for use as an intervention tool. Furthermore, the implementation of the Trait and Factor counselling approach demonstrated improvements in students’ career decision-making abilities, enabling them to make choices more confidently and purposefully. The study highlights the importance of utilizing theoretically grounded and validated guidebooks to support more structured and effective career counselling practices.